Epigenetic Regulations in Neuropsychiatric Disorders - Kuehner, Janise N.; Bruggeman, Emily C.; Wen, Zhexing; Yao, Bing (Frontiers in Genetics, 2019)
Precise genetic and epigenetic spatiotemporal regulation of gene expression in the mammalian central nervous system is critical in how the brain develops, functions and forms its complex circuitry between differentiated neurons. These neuronal differentiation processes are tightly regulated by epigenetic processes including DNA methylation, histone modifications and non-coding RNAs. Dysregulation of any of these pathways is detrimental to normal neuronal development and functions, which can result in devastating neuropsychiatric disorders, such as depression, schizophrenia, and autism spectrum disorders. In this review, we focus on the current understanding of epigenetic regulations in brain development and functions, as well as their implications in neuropsychiatric disorders.